A Longitudinal Peri-Implant Diaphyseal Fracture Around a Locked Humeral Nail: A Case Report - Ana del Potro Jareño; Alfonso González Menocal; Ana Antonia Couceiro Laredo; Laura Conde Ruiz; Daniel López Dorado (Reports)
Background and Clinical Significance: Non-prosthetic peri-implant fractures (NPPIFs) are rare injuries occurring around internal fixation devices, and are distinct from periprosthetic fractures. While most studies focus on the femur, humeral NPPIFs remain poorly documented. This case illustrates a complex humeral NPPIF and highlights key surgical considerations. Case Presentation: A 62-year-old woman presented with a spiral humeral shaft fracture (AO 12B2) after a fall. Following closed reduction and antegrade intramedullary nailing, an intraoperative peri-implant fracture occurred at the distal interlocking screw. CT imaging revealed a complex fracture extending from the lateral condyle to the proximal humerus. Treatment included implant removal and open reduction with dual plate fixation—lateral distal and helically contoured proximal plates—plus cerclage bands and antibiotic-loaded beads. Recovery was uneventful, with a full range of motion achieved at six months. At one year, the DASH score and MEPS were 86 and 75, respectively. Conclusions: Humeral NPPIFs are challenging and require individualized, biomechanically sound strategies. This case reinforces the importance of intraoperative assessment and careful implant selection in humeral fracture management.